COMPARISON OF COFFEE FARMING WITH MONOCULTURE AND POLYCULTURE CROPPING PATTERNS IN KARO REGENCY (CASE STUDY IN TIGA PANAH DISTRICT AND BARUSJAHE DISTRICT) - Muhammad Mu’arif Nasution; Zulkarnain Lubis; Syahbudin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Karo Regency is one of the coffee growing centers in Indonesia. Karo Regency is a regency in North Sumatra Province. Several sub-districts produce the most coffee and have the largest land area, namely Tiga Panah and Barusjahe Districts. In addition to coffee, Karo Regency is a major center for vegetables, especially cabbage. To increase farmers' incomes, given their limited land and planting area, farmers must increase the production of each coffee plot. One way to do this is through polyculture planting, which involves intercropping coffee plants. The purpose of this study was to comparatively analyze coffee farming practices that implement monoculture and polyculture in Karo Regency and to determine the factors that influence coffee farmers' income in both cropping patterns and the influence of cropping patterns on the long-term sustainability of coffee farming. The research design used was comparative quantitative research. The method for determining the location in the study used purposive sampling and simple random sampling. The sample in this study were coffee farmers in Karo Regency who implement monoculture and polyculture cropping patterns. with a total of 60 people, 30 farmers cultivate monoculture coffee plants and 30 polyculture coffee farmers spread across 2 (two) sub-districts, namely Tiga Panah Sub-district and Barusjahe Sub-district.